Innovative coding schemes for cooperative multihop radio systems - James, Ashish (2012)
Cooperative communication with its distributed structure is considered as a promising energy efficient paradigm for future green radio communications. In such systems, multiple wirelessly communicating devices cooperate with each other to create a network of wireless nodes with virtual antenna arrays. Such wireless networks with an omnidirectional antenna exhibit some distinct and interesting properties. The most pivotal one is that the transmissions are broadcast by nature which enables the nodes within its vicinity to overhear the transmissions. This enables the intermediate nodes to process the overheard information and cooperate in transmissions. However, the realization of such schemes for wireless multihop networks is challenging, owing to the lack of bandwidth efficiency and the coordination overheads required for reliably transmitting the information to the receiver.